Challenges in Safeguarding Rights for Child indigenous faiths - Kusmayanti, Hazar; Rubiati, Betty; Mulyanti, Asti Sri; Suparto, Susilowati (Jurnal Bina Mulia Hukum, 2024)
A child of a indigenous faiths community is someone who has grown up in a community that holds certain traditional beliefs or faiths, which are often local and not tied to a major religion or official doctrine. They may follow or practice traditions such as the worship of nature, ancestral spirits, or rituals passed down through generations. In general, protection for minority groups. This research will examine the problematic fulfillment of children's rights of indigenous faiths in Indonesia. The approach method used in the research is normative juridical through legal principles, legal systematics, legal synchronization, and legal comparison. The data analysis method is qualitative juridical obtained through primary, secondary and tertiary data related to case studies of the fulfillment of children's rights of indigenous peoples in the region. The results of the research obtained from the problematic fulfillment of children's rights of indigenous faiths, first, the lack of legal recognition and identity/rejection of childbirth certificate registration for indigenous faiths couples. Second, the right of children to receive education in accordance with the curriculum and teachings of their beliefs. Third, protection from discrimination: Children from indigenous faith communities may be vulnerable to discrimination, and fourth, freedom of religion. The right of children to choose and practice their own religion or belief should be respected and protected.